Carbon stocks of intact mangroves and carbon emissions arising from their conversion in the Dominican Republic - Kauffman, J.B.; Heider, C.; Norfolk, J.; Payton, F. (Wiley, 2014)
Mangroves are recognized to possess a variety of ecosystem services including high rates of carbon sequestration and storage. Deforestation and conversion of these ecosystems continue to be high and have been predicted to result in significant carbon emissions to the atmosphere. Yet few studies have quantified the carbon stocks or losses associated with conversion of these ecosystems. In this study we quantified the ecosystem carbon stocks of three common mangrove types of the Caribbean as well as those of abandoned shrimp ponds in areas formerly occupied by mangrove—a common land‐use conversion of mangroves throughout the world. In the mangroves of the Montecristi Province in Northwest Dominican Republic we found C stocks ranged from 706 to 1131 Mg/ha. The medium‐statured mangroves (3–10 m in height) had the highest C stocks while the tall (>10 m) mangroves had the lowest ecosystem carbon storage. Carbon stocks of the low mangrove (shrub) type (<3 m) were relatively high due to the presence of carbon‐rich soils as deep as 2 m. Carbon stocks of abandoned shrimp ponds were 95 Mg/ha or ∼11% that of the mangroves. Using a stock‐change approach, the potential emissions from the conversion of mangroves to shrimp ponds ranged from 2244 to 3799 Mg CO2e/ha (CO2 equivalents). This is among the largest measured C emissions from land use in the tropics. The 6260 ha of mangroves and converted mangroves in the Montecristi Province are estimated to contain 3 841 490 Mg of C. Mangroves represented 76% of this area but currently store 97% of the carbon in this coastal wetland (3 696 722 Mg C). Converted lands store only 4% of the total ecosystem C (144 778 Mg C) while they comprised 24% of the area. By these metrics the replacement of mangroves with shrimp and salt ponds has resulted in estimated emissions from this region totaling 3.8 million Mg CO2e or ∼21% of the total C prior to conversion. Given the high C stocks of mangroves, the high emissions from their conversion, and the other important functions and services they provide, their inclusion in climate‐change mitigation strategies is warranted.